Something is out of place: characteristics of suicide attempted cases admitted at an emergency room of a large-sized hospital (Research, Society and Development, 2020)
Such an article aimed to discuss the main characteristics of suicide attempted cases admitted at an emergency room of a large-sized hospital of the Northern Region of Ceará State. An exploratory descriptive study with transversal design. Data collection was performed using a specific form filled in with existing information in the medical records of 153 individuals who attempted suicide. Regarding sociodemographic profile, 50,3% (n=77) were male; 54,2% (n= 83) with age range from 21 to 41 years old; 60,0% (n=78) having incomplete elementary schooling; and 29,4% (n=45) reported to be unemployed. Referring to age and gender variables, we observed a greater number of occurrences of attempted suicide among women range-aged of 12 and 21 years-old. As for the method, over 30% ingested poison. Male gender chose the most aggressive or lethal methods. About the evolution of cases, 55,55% progressed well with clinical improvement and hospital discharge. Such information will be useful for health professionals and managers who intend to develop actions for mental health promotion focusing on reducing the number of attempted suicides.